Economic growth and renewable energy consumption in Asia: Does good governance moderate the trade-off? - Quyen Le Hoang Thuy To Nguyen; Thu Quang Anh Pham (International Journal of Renewable Energy Development, 2026)
This study examines the trade-off between economic growth and renewable energy consumption in 31 Asian economies over the period 1996-2023, with a focus on the moderating role of governance quality. Using fixed-effects panel estimation, with country-clustered standard errors, we construct a multi-dimensional governance quality index based on Principal Component Analysis (PCA). The findings suggest that economic growth is associated with a statistically significant decline in the share of renewable energy consumption (β=-13.59, p<0.01). In semi-log terms, a 1% increase in GDP per capita is associated with a 0.136 percentage-point reduction in renewable energy consumption share, implying the presence of growth-induced fossil fuel dependence. However, the interaction term between growth and governance is positive and significant (β=1.73, p <0.05), indicating that stronger governance quality mitigates this adverse effect. Further analysis using an environmental Kuznets curve (EKC) specification reveals a U-shaped relationship between income and renewable energy consumption. Sensitivity analysis using disaggregated governance indicators shows that government effectiveness and regulatory quality are the key institutional dimensions driving this moderating effect. Subsample analysis further uncovers significant heterogeneity across income groups. While the trade-off is prominent in lower-middle and upper-middle income economies, high-income countries exhibit a positive growth-renewable energy consumption nexus. The results remain robust when using lagged explanatory variables. This study contributes to the literature by providing cross-country evidence of a fossil lock-in effect in Asia and by identifying governance quality as a moderating institutional mechanism shaping the energy transition. The findings underscore the importance of strengthening institutional quality to align economic growth with renewable energy development in heterogeneous Asian contexts.